2005
DOI: 10.1177/1056492605276850
|View full text |Cite
|
Sign up to set email alerts
|

Publish or Perish

Abstract: There are few more familiar aphorisms in the academic community than “publish or perish.” Venerated by many and dreaded by more, this phenomenon is the subject of the authors’ essay. Here they consider the publish or perish principle that has come to characterize life at many business schools. They explain when and why it began and suggest reasons for its persistence. This exercise elicits questions that appear as relatively neglected but are integral to our profession, namely, the effect of publish or perish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
18

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(99 citation statements)
references
References 20 publications
0
81
0
18
Order By: Relevance
“…The data are split. On the one hand, the literature supports the idea that departments are decreasing the number of full time tenured positions to offer more flexible, part-time positions off the tenure-track (Jacobs, 1998;Rhoades, 1996) due to budgetary constraints and the increasing pressure for tenured and tenure-track faculty for research (De Rond & Miller, 2005;Euben, 2002;Neill, 2008;& Parker et al, 1998). On the other hand, this research showed tenured and tenure-track faculty teach more courses and more students than their counterparts.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The data are split. On the one hand, the literature supports the idea that departments are decreasing the number of full time tenured positions to offer more flexible, part-time positions off the tenure-track (Jacobs, 1998;Rhoades, 1996) due to budgetary constraints and the increasing pressure for tenured and tenure-track faculty for research (De Rond & Miller, 2005;Euben, 2002;Neill, 2008;& Parker et al, 1998). On the other hand, this research showed tenured and tenure-track faculty teach more courses and more students than their counterparts.…”
Section: Discussionmentioning
confidence: 75%
“…Plus, the primary measure of research activity used in tenure decisions is the number of publications (Allen, 1996;Blackburn & Lawrence, 1995;Bland et al, 2006;Fairweather, 2005). Although the number of publications is used to assess faculty productivity, it is not evidence of research quality (Colbeck, 2004), thus many in academia are concerned with the pressure to publish in order to be productive (De Rond & Miller, 2005;Euben, 2002;Neill, 2008;and Parker, Guthrie, & Gray, 1998). For this study the National Study of Postsecondary Faculty (NSOPF: 04) referred to research in the number of: articles or creative works in referred and non-referred journals; reviews of books, articles, creative works, chapters in edited books; textbooks other books, monographs, and client reports; presentations at conferences or workshops; career exhibitions or performances; and patents, software, products, or other works.…”
Section: Researchmentioning
confidence: 99%
“…Avaliação de desempenho de acadêmicos, orientação do sistema de promoções, remuneração, aquisição de estabilidade (tenure) e acesso a recursos de pesquisa (Rond & Miller, 2005;Starbuck, 2005;Van Dalen & Henkens, 2012) são exemplos de decisões nas quais a publicação científica desempenha um papel relevante. Nesses termos, a publicação de artigos se tornou elemento-chave na avaliação da produtividade científica dos acadêmicos, tendo como suporte as métricas e rankings que foram associados a essa forma de produção acadêmica (Adler & Harzing, 2009;Domingues, 2014;Horta & Santos, 2016;Parker et al, 1998).…”
Section: Publicações Científicas Produtividade E Perfil De Acadêmicosunclassified
“…62-83, Jan./Fev. 2017 www.anpad.org.br/rac periódicos, o imperativo de avaliação da carreira de acadêmicos baseada na quantidade de publicações, o gradual abandono de outras formas de publicação e premiações por número de publicações são alguns dos aspectos observados na literatura sobre o predomínio de publicações em periódicos indexados (Alcadipani, 2011;Rond & Miller, 2005;Van Dalen & Henkens, 2012).…”
Section: Publicações Científicas Produtividade E Perfil De Acadêmicosunclassified
See 1 more Smart Citation